AEGIS: Infrared spectroscopy of an infrared-luminous lyman break galaxy at z = 3.01 - Huang, J; Rigopoulou, D; Papovich, C; Ashby, M; Willner, S; Ivison, R; Laird, E; Webb, T; Wilson, G; Barmby, P; Chapman, S; Conselice, C; et al. (Institute of Physics Publishing, 2007)
We report the detection of rest-frame 6.2 and 7.7 μm emission features arising from polycyclic aromatic hydrocarbons (PAHs) in the Spitzer IRS spectrum of an infrared-luminous Lyman break galaxy at z = 3.01. This is currently the highest redshift galaxy where these PAH emission features have been detected. The total IR luminosity inferred from the MIPS 24 μm and radio flux density is 2 × 1013 L⊙, which qualifies this object as a so-called hyperluminous infrared galaxy (HyLIRG). However, unlike local HyLIRGs, which are generally associated with QSO/AGNs and have weak or absent PAH emission features, this HyLIRG has very strong 6.2 and 7.7 μm PAH emission. We argue that intense star formation dominates the IR emission of this source, although we cannot rule out the presence of a deeply obscured AGN. This LBG appears to be a distorted system in the HST ACS F606W and F814W images, possibly indicating that a significant merger or interaction is driving the large IR luminosity. © 2007. The American Astronomical Society. All rights reserved.